Morfologia e sedimentologia da praia de macromaré de Ajuruteua, Pará: um estudo para definição de índices de sensibilidade ambiental ao derramamento de óleo - BRAGA, Francisca de Paula da Silva (Universidade Federal do Pará, 2019)
The Ajuruteua macrotidal beach located in Northern Brazil is subject to oil pollution in response to the routes of tanker ships. Hence, it is very important to know the environmental characteristics to establish contingency plans. The aim of this work is to investigate the spatial and seasonal changes in grain size and morphologic properties along the intertidal zone (IZ) to define environmental sensitivity index (ESI) to oil spill in this beach zone. During this research it was carried out 23 beach profiles from foredunes to 1 m in deep in the subtidal zone under low spring tide condition. Along this profiles, sedimentary samples were collected in June, September and December 2005 (solsticious) and March 2006 (equinoctials). Sedimentary samples were analyzed in laser granulometer (Malvern Mastersize 2000) in 1/8φ interval. Topographical data were collected by TOPCON total station and processed using TOPOGRAPH 98SE and GOLDEN SOFTWARE (SUFER 8.0). The results show seasonal variations in the grain size and morphologic distribution in the IZ. On June and December the IZ is flat, while on March and September we observe the occurrence of a ridge and runnel system. On June and December, the upper IZ sediments are fine, well sorted, with positive skewness, tending to be coarser in direction to lower IZ, where the sediments are moderately to poorly sorted, with negative skewness. On September and March, it was observed heterogeneity on IZ sediment distribution; the grain size changes from fine to medium, from well to poorly sorted, with negative skewness. In the runnel, the sediments tend to be coarser with negative skewness and moderately sorting. To Ajuruteua beach ESI map elaboration we classified the index 3A as less sensible and the index 3E as more sensible. On June and December the lower IZ is more sensible (index 3D) to oil spill than upper IZ (index 3A). On March and September, the sensibility is higher, mainly along the runnel (3E), that work out as a trap, difficulting the oil cleaning.